Design and Build a Web-based Management Information System at CV Sanjaya Abadi Baru - Steven Famy; Tukino Tukino (Universitas Medan Area, 2022)
Competition in running a business at this time is tight, companies that do not utilize technology will be left behind from their competitors. Therefore, it is necessary to implement technology such as the System Information Management into the company’s business processes. This research was conducted at one of the developing companies in city of Batam named “CV. Sanjaya Abadi Baru”. In this research, the author uses research method called Agile Scrum, this research method is a popular method to manage application development project and helps in building application quickly, this method uses Backlog as a list of features that need to be implemented, Sprint as a time cycle rule in working on a task and the Daily Scrum to update the work process on daily basis. Author also includes diagram design, detailed design, implementation result, and system testing. The conclusion result from this research is that the system information management built for CV. Sanjaya Abadi Baru is proven to be more effective and efficient than the old company system in the company's business processes to store, process data and obtain information that influences decision making within the company and helps prospective customers to get the information needed more quickly, precisely and accurately.